Modeling ambient airflow in the aluminum electrolysis cell superstructure - Sarah Elizabeth DiBenedetto 1997- (2021)
This project concerns the development of a rudimentary CFD model for the ambient airflow inside of the aluminum electrolysis cells at the Icelandic aluminum smelter Norðurál. Research efforts are currently being made in the Icelandic aluminum industry to dramatically decrease the associated CO2 emissions and eventually become carbon neutral. One suggested method for emissions reduction is the utilization of geologic carbon capture and sequestration in the basalt rock, which can be throughout Iceland. In order to operate carbon capture at the aluminum smelter, the concentration of carbon dioxide in the cell effluents needs to be increased from the current value of 1 vol % to 4 vol %. This may be done through modifications of the cell superstructure and through adjusting the draft rate of ambient air through the cell. The electrochemical production of aluminum operates at very high temperatures, and the heat balance of the cell must be maintained. CFD modeling of the top cell is a crucial component in understanding the heat balance of the cell and the effects of operational changes on the heat balance. Over half of the heat loss in the cell occurs through the superstructure, and the majority of these losses are through the exhaust gas. The model presented in this study was used to establish the effect of cell draft rate on the pressure drop inside of the cell and the exhaust gas temperature. The results from the model show that utilizing a pressure outlet is satisfactory for controlling the simulated cell draft rate and mass flow rate through the cell. A mass flow outlet was used to determine the relationship between the exhaust temperature and the cell draft rate. Comparisons between the simulation scenarios and literature are provided as well as recommendations for future development of the CFD model. Í þessu verkefni var þróað CFD líkan fyrir loftstreymi og afsog inni í yfirbyggingu ál rafgreiningarkerja álvers Norðuráls á Grundartanga. Verkefnið er liður í rannsókna- og þróunarátaki íslensks áliðnaðar til að ...